Europe and Africa: One continent in the university education - Nathalie Nzekwa; Mohamed Ahmed Jimale; Alma Orazi; Vittorio Colizzi; Nicaise Ndembi (AOSIS, 2023)
The Erasmus Programme is the EU programme that allows students to travel to countries in the European Union. Erasmus+ is the new programme combining all the EU's current schemes for education, training, youth and sport, which was started in January 2014 and will be held for the period 2021-2027. It stands for European Region Action Scheme for the Mobility of University Students+ [...].